Relation of hepatitis B core antigen expression with histological activity, serum HBeAg, and HBV DNA levels - Aysegul Sari; Yelda Dere; Betul Pakoz; Aylin Calli; Belkis Unal; Mine Tunakan (Wolters Kluwer Medknow Publications, 2011)
Background: Hepatitis B virus (HBV) is a potentially life-threatening liver infection which may progress to liver failure and cirrhosis. Intrahepatic expression patterns of viral antigens detected by immunohistochemistry may have prognostic implications in disease process. Aim: In this study, we aimed to investigate the relationship between the HBV core antigen (HBcAg) expression and histological activity index (HAI), fibrosis, serum hepatitis B e-antigen (HBeAg) status and HBV DNA levels in patients with chronic HBV infection. Materials and Methods: A total of 114 liver biopsies from patients with chronic HBV infection were included in the study. Immunohistochemical expression of HBcAg and its relation with HAI, fibrosis, serum alanine aminotransferase (ALT) levels, HBeAg status and HBV DNA levels were assessed. Results: The presence of nuclear expression of HBcAg did not show any correlations with ALT levels, HAI and fibrosis score. When the groups were categorized according to the HBeAg status, nuclear HBcAg expression was found to be high in HBeAg positive patients. However, HBcAg nuclear expression showed significant correlations with HBV DNA levels and fibrosis scores in HBeAg negative but not HBeAg positive patients. HBV DNA levels were also significantly associated with HAI and fibrosis scores in HBeAg negative patients. Conclusions: Significant differences found between HBeAg positive and negative patients suggest that HBeAg negative disease is different from HBeAg positive disease, and also point outs that in HBeAg negative disease, patients with nuclear HBcAg expression and increased levels of HBV DNA levels are at a higher risk of developing progressive liver disease.